A mild method for regioselective labeling of aromatics with radioactive iodine - Rønnest, Mads H.; Nissen, Felix; Pedersen, Palle J.; Larsen, Thomas O.; Mier, Walter; Clausen, Mads H. (European journal of organic chemistry, 2013)
A novel technique to label ortho-, meta-, and para-trimethylsilyl-substituted aryl substituents with radioactive iodide is described. The method takes advantage of the ipso-directing and activating properties of trimethylsilyl substituents on the arenes. The method was demonstrated on a griseofulvin analogue with promising anticancer properties and on lidocaine, a widely used local anesthetic drug. Treatment of a trimethylsilyl precursor with Tl(OCOCF3)3 followed by Na125I consistently afforded radioactive purities over 95 % in all cases.
Gesehen am 19.01.2022